PENGARUH KINERJA KEUАNGАN DАN GOOD CORPORATE GOVERNANCE TERHADAP HАRGА SАHАM YАNG DIMΟDERАSI ΟLEH INTERNET FINANCIAL REPORTING - Herlina Putri Rianti; Аjeng Wijаyаnti (International Journal of Digital Entrepreneurship and Business, 2021)
The purpose of this study was to analyze the influence of financial performance [Economic Value Added (EVA), Market Value Added (MVA)], Good Corporate Governance [Board of Commissioners (BoC), institutional ownership (IO)], and Internet Financial Reporting (IFR) on stock prices. With IFR to moderate EVA, MVA, BoC and IO on stock prices. The research samples are manufacturing companies with consumption products that listed on the Indonesian Stock Exchanges (IDX) from 2014 to 2019. The sampling technique used in this research is purposive sampling and to test the hypothesis, STАTА software is used in analyzing the data. The results show that MVA has significant influence stock prices. However, EVA, BoC, IO and IFR could not influence stock prices. For IFR could moderate EVA, and MVA to influence stock prices. Though, IFR could not moderate BoC and IO to influence stock prices. The practical implication for this study, is helping the investor for decision making by not considering only for financial performance, but also good corporate governance.